Evaluation of anti-coccidial drug sensitivity against experimental coccidiosis in broiler chicks (Journal of the Bangladesh Agricultural University, 2016)
This study was undertaken to investigate the effect of sulphaclozine sodium and toltrazuril for the treatment of experimentally induced caecal coccidosis. Day-old chicks (n=96) reared in a coccidia free condition divided into six Groups (A, B, C, D, E and F) each having 4 subgroups of 4 chicks in each. At the age of 23 days the chicks were infected with 104 sporulated oocysts of E. tenella except control Group F and treated for 4 consecutive days from 3 days post infection. Then treatment was given in Group A (2 gm/L), B (3 gm/L) with sulphaclozine sodium and in Group C (1 ml/L), D (1.5 ml/L) with toltrazuril. Group E was maintained as infected, but untreated and Group F as negative control. After treatment Group A gained almost similar weight with Group F. A significantly higher (P